2014
DOI: 10.4236/oalib.1100414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Polyphenol Content and Antioxidant Activity in Extracts of Cucurbita spp

Abstract: It is increasingly evident that oxidative stress and the presence of free radicals are a major cause of many disease processes that may aggravate the disease course, or create new effects that could cause further alterations in patient's health or impair their quality of life. The purpose of this study was to determine the antioxidant activity of extracts from seeds of four varieties of Cucurbita spp: (Hybrid between C. moschata and C. maxima Duchesne ex Lam) Tetsukabuto, C. mixta Pangalo (calabaza rayada), C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
(14 reference statements)
4
8
1
3
Order By: Relevance
“…Phenols reduce the phosphomolybdic acid present in the Folin-Ciocalteu reagent from yellow to green. (11) Of all extracts ethyl acetate extract of the peel showed the highest phenolic content. Hexane extracts of both peel and seed showed more or less the same phenolic content.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Phenols reduce the phosphomolybdic acid present in the Folin-Ciocalteu reagent from yellow to green. (11) Of all extracts ethyl acetate extract of the peel showed the highest phenolic content. Hexane extracts of both peel and seed showed more or less the same phenolic content.…”
Section: Discussionmentioning
confidence: 95%
“…(10) The total phenolic content in the six extracts were estimated by Folin-Ciocalteu method using Gallic acid as the standard. (11) The reagent is formed from a mixture of phosphotungstic acid and phosphomolybdic acid. Phenols reduce the phosphomolybdic acid present in the Folin-Ciocalteu reagent from yellow to green.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that the polyphenolic content varied depending on the type of extract. The concentration of polyphenols in the ethanol extract was 40.37 mg/g GAE, in the aqueous extract-40.12 mg/g GAE, butanol extract-92.62 mg/g GAE, ethyl acetate extract-85.12 mg/g GAE, chloroform extract-21.25 mg/g GAE, and n-hexane extract-12.50 mg/g GAE [49]. Oloyede et al conducted research on the content of total polyphenols in pumpkin pulp (Cucurbita pepo Linn.).…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 95%
“…Pumpkins are widely used in Korea as healthy and functional vegetables, because they are rich in phenolics, flavonoids, vitamin A and C, β-carotene, α-tocopherol, amino acids, carbohydrates, minerals, and fibers. Pumpkins are known to have physiological activities such as anticancer, antioxidant, and anti-obesity ( 10 – 13 ). Pumpkin leaves have distinct taste and texture and are used as Korean cuisine “ ssam ” to wrap a piece of meat such as pork or other filling accompanied by a condiment.…”
Section: Introductionmentioning
confidence: 99%